2004
DOI: 10.1007/s00415-004-1505-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimising MS disease-modifying therapies: antibodies in perspective

Abstract: A proportion of people with multiple sclerosis (MS) treated with interferon (IFN) a develop neutralising anti-IFN beta antibodies (NABs). The immunogenicity of the available commercial compounds relates to the genetic structure of the IFN beta molecule, its mode of production, glycosylation status, aggregate formation, commercial formulation, potency, dose, frequency and, possibly, route of administration. At present, it is not possible to predict who will develop NABs usually appear within the first 2 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For this reason, most reported studies have used the level of CPE inhibition to assess NAb presence and titer during MS therapy; however, variation in assay procedures (including cell line employed, serum dilution protocols, and 'reference' dose of IFN␤) have made comparing results from different laboratories difficult [13,14].…”
Section: Factors Influencing Reported Incidence Of Nabsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, most reported studies have used the level of CPE inhibition to assess NAb presence and titer during MS therapy; however, variation in assay procedures (including cell line employed, serum dilution protocols, and 'reference' dose of IFN␤) have made comparing results from different laboratories difficult [13,14].…”
Section: Factors Influencing Reported Incidence Of Nabsmentioning
confidence: 99%
“…In order to assess the clinical significance of NAbs, it is particularly crucial that standard cutoff values be established to classify patients as NAb positive or NAb negative [14]. Ideally, these values should also bear some relationship to a clinically meaningful attenuation of IFN␤ function.…”
Section: Factors Influencing Reported Incidence Of Nabsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although direct comparisons among many of the studies is difficult because of the use of different neutralization assays and standards, comparative studies have shown that IFN-β1b is more immunogenic than IFN-β1a (Bertolotto and others 2002), possibly because of the lower specific activity of IFN-β1b and, hence, the higher protein mass injected. Amino acid differences and lack of glycosylation of IFN-β1b compared with the native protein or currently licensed recombinant forms of IFN-β1a or formulation characteristics may also contribute to the immunogenicity of IFN-β1b (Giovannoni 2004).…”
Section: Introductionmentioning
confidence: 99%